2019
DOI: 10.3892/mmr.2019.9836
|View full text |Cite
|
Sign up to set email alerts
|

Coculture with bone marrow‑derived mesenchymal stem cells attenuates inflammation and apoptosis in lipopolysaccharide‑stimulated alveolar epithelial cells via enhanced secretion of keratinocyte growth factor and angiopoietin‑1 modulating the Toll‑like receptor‑4 signal pathway

Abstract: Acute lung injury (ALI) is a common, costly and potentially lethal disease with characteristics of alveolar-capillary membrane disruption, pulmonary edema and impaired gas exchange due to increased apoptosis and pulmonary inflammation. There is no effective and specific therapy for ALI; however, mesenchymal stem cells (MSCs) have been demonstrated to be a potential option. Lipopolysaccharide (LPS) is a highly proinflammatory molecule that is used to mimic an in vivo inflammatory and damaged state in vitro. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In vivo administration of MSCs into ARDS models can reduce the apoptotic cell counts in the lung tissues and distal organs in ARDS (Silva et al, 2018). MSCs have also been reported to reduce apoptosis of the alveolar epithelial cells and endothelial cell by secretion of keratinocyte growth factor (KGF), angiopoietin -1, and HGF (Bernard et al, 2018;Chen et al, 2019a;Meng et al, 2019). Alveolar macrophage apoptosis induced by lipopolysaccharide (LPS) was also attenuated after MSC treatment, which may be partially mediated by inhibition of the Wnt/β-catenin pathway (Li et al, 2015).…”
Section: Review Reduction Of Cell Apoptosismentioning
confidence: 99%
“…In vivo administration of MSCs into ARDS models can reduce the apoptotic cell counts in the lung tissues and distal organs in ARDS (Silva et al, 2018). MSCs have also been reported to reduce apoptosis of the alveolar epithelial cells and endothelial cell by secretion of keratinocyte growth factor (KGF), angiopoietin -1, and HGF (Bernard et al, 2018;Chen et al, 2019a;Meng et al, 2019). Alveolar macrophage apoptosis induced by lipopolysaccharide (LPS) was also attenuated after MSC treatment, which may be partially mediated by inhibition of the Wnt/β-catenin pathway (Li et al, 2015).…”
Section: Review Reduction Of Cell Apoptosismentioning
confidence: 99%
“…42 It has been reported that MSCs can reduce apoptosis of the alveolar epithelial cells and endothelial cell by secretion these three growth factors. [77][78][79] The VEGF and FGF secreted by MSCs can also promote lung tissue repair. 80,81 In addition, MSCs can reduce the levels of pro-fibrotic factors to The MSC-like IMRCs could also reverse pulmonary fibrosis by overexpressing the matrix metalloproteinase MMP1 and reducing collagen I levels during fibrogenesis induced by TGF-β1.…”
Section: Tissue Repair and Regeneration Capabilities Of Mscsmentioning
confidence: 99%
“…Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common and devastating clinical disorders characterized by increased non-hydrostatic extravascular lung water, reduced pulmonary compliance, and acute hypoxemic respiratory failure [1]. Despite substantial progress in mechanical ventilatory strategies, significant advances in the quality of care of critically ill patients, and an enhanced understanding of molecular mechanisms, the mortality rate among patients with ALI/ARDS remains unacceptably high [2,3].…”
Section: Introductionmentioning
confidence: 99%